Modeling of the 2.4 GHz wireless channel path loss in substation - Qiang LI; Hongxin ZHANG; Jiaqi LUO; Yang LU; Jianqi LI; Yinghua LV (Dianxin kexue)
In order to assess the influence of electromagnetic interference in the substation of the electric power communication system,frequency measurement method was adopted to obtain the data of 2.4 GHz electromagnetic wave path loss of the substation of 110 kV and 220 kV in a certain city.By using the method of minimum mean square error (MMSE) and cumulative sum (CUSUM) to estimate the parameters of path loss model such as path loss index and the standard deviation,the path loss model was set up according to measured data,respectively.The simulation results show that the gap between estimation results and the measured values is not big.In addition,a ZigBee simulation system was constructed to simulate the relationship of bit error rate (BER) varies with distance in two cases of the signal to noise ratio (SNR) at 5 dB and 10 dB respectively.A research basis for short distance wireless communication devices decorated in the substation environment was provided.